Rapid adaptation through genomic and epigenomic responses following translocations in an endangered salmonid. (6th July 2021) - Crotti, Marco; Yohannes, Elizabeth; Winfield, Ian J.; Lyle, Alex A.; Adams, Colin E.; Elmer, Kathryn R.
Abstract: Identifying the molecular mechanisms facilitating adaptation to new environments is a key question in evolutionary biology, especially in the face of current rapid and human‐induced changes. Translocations have become an important tool for species conservation, but the attendant small population sizes and new ecological pressures might affect phenotypic and genotypic variation and trajectories dramatically and in unknown ways. In Scotland, the European whitefish ( Coregonus lavaretus ) is native to only two lakes and vulnerable to extirpation. Six new refuge populations were established over the last 30 years as a conservation measure. In this study, we examined whether there is a predictable ecological and evolutionary response of these fishes to translocation. We found eco‐morphological differences, as functional traits relating to body shape differed between source and refuge populations. Dual isotopic analyses suggested some ecological release, with the diets in refuge populations being more diverse than in source populations. Analyses of up to 9117 genome‐mapped SNPs showed that refuge populations had reduced genetic diversity and elevated inbreeding and relatedness relative to source populations, though genomic differentiation was low ( F ST = 0.002–0.030). We identified 14 genomic SNPs that showed shared signals of a selective response to translocations, including some located near or within genes involved in the immune system, nervous system and hepatic functions. Analysis of up to 120, 897 epigenomic loci identified a component of consistent differential methylation between source and refuge populations. We found that epigenomic variation and genomic variation were associated with morphological variation, but we were not able to infer an effect of population age because the patterns were also linked with the methodology of the translocations. These results show that conservation‐driven translocations affect evolutionary potential by impacting eco‐morphological, genomic and epigenomic components of diversity, shedding light on acclimation and adaptation process in these contexts.